Differential anti-glycan antibody responses in Schistosoma mansoni-infected children and adults studied by shotgun glycan microarray. - Angela van Diepen; Cornelis H Smit; Loes van Egmond; Narcis B Kabatereine; Angela Pinot de Moira; David W Dunne; Cornelis H Hokke (PLoS Neglected Tropical Diseases)
Background Schistosomiasis (bilharzia) is a chronic and potentially deadly parasitic disease that affects millions of people in (sub)tropical areas. An important partial immunity to Schistosoma infections does develop in disease endemic areas, but this takes many years of exposure and maturation of the immune system. Therefore, children are far more susceptible to re-infection after treatment than older children and adults. This age-dependent immunity or susceptibility to re-infection has been shown to be associated with specific antibody and T cell responses. Many antibodies generated during Schistosoma infection are directed against the numerous glycans expressed by Schistosoma. The nature of glycan epitopes recognized by antibodies in natural schistosomiasis infection serum is largely unknown. Methodology/principal findings The binding of serum antibodies to glycans can be analyzed efficiently and quantitatively using glycan microarray approaches. Very small amounts of a large number of glycans are presented on a solid surface allowing binding properties of various glycan binding proteins to be tested. We have generated a so-called shotgun glycan microarray containing natural N-glycan and lipid-glycan fractions derived from 4 different life stages of S. mansoni and applied this array to the analysis of IgG and IgM antibodies in sera from children and adults living in an endemic area. This resulted in the identification of differential glycan recognition profiles characteristic for the two different age groups, possibly reflecting differences in age or differences in length of exposure or infection. Conclusions/significance Using the shotgun glycan microarray approach to study antibody response profiles against schistosome-derived glycan elements, we have defined groups of infected individuals as well as glycan element clusters to which antibody responses are directed in S. mansoni infections. These findings are significant for further exploration of Schistosoma glycan antigens in relation to immunity.